Investigation of thermomechanical analysis of carbon/epoxy composite for spacecraft structure material - Ibadi, Mahfud; Purnomo, Herry; Vicarneltor, David Natanael; Wibowo, Heri Budi; Setianto, Muhamad Hananuputra; Whulanza, Yudan (Penerbit Universiti Kebangsaan Malaysia, 2024)
When building spacecraft structures, it is crucial to use lightweight and high-strength composite materials with the necessary characteristics. Aerospace applications benefit significantly from the exceptional properties of carbon/ epoxy composite materials. As part of a study on composite materials, this work focuses on exploring the thermomechanical properties of carbon fiber. The matrix used in this research is LY-5052 epoxy, applied through a vacuum infusion technique. To achieve optimal composite properties, various tests are conducted to evaluate its thermomechanical behavior. These tests may include measuring Thermal Conductivity and performing thermogravimetric analysis (TGA). Most importantly, the composite is subjected to tensile testing at room temperature to 200 °C. This is done because most tensile tests on carbon/LY5052 composites are carried out at room temperature. The results obtained from the measurement of the thermal conductivity of the carbon/LY5052 composite were 0.419 W/mK; from the Thermogravimetric Analysis (TGA), the carbon/LY5052 composite began to decompose at a temperature of 365.63 °C and the tensile test was carried out simultaneously with variations in temperature from room temperature, 50 °C, 100 °C, 150 °C and 200 °C have tensile strengths of 553, 507, 340, 266, and 242 MPa, respectively. This trend confirms that strength decreases with higher temperature loads. Several image observations are also presented in this report to understand composite materials’ failure behavior at these various temperatures.